FIELD FORMATION OF CIRCULANT MATRIX - Fahlevi, Mahfudz Reza (PATTIMURA UNIVERSITY, 2020)
The axioms of fields satisfy over sets of numbers such as , , and . Generally, a set matrix is not commutative for binary multiplication properties, such that cannot satisfy of field axioms. In this paper we will discuss the circulant matrix set which satisfies the commutative properties of multiplication, then it will be shown that the definition of a field is satisfied by the circulant matrix . This can provide a new perspective on a field formed by matrix.